Effect of Cannabidiol Oil on Post-ureteroscopy Pain for Urinary Calculi: A Randomized, Double-blind, Placebo-controlled Trial. Issue 4 (9th April 2023) - Narang, Gopal; Moore, Jonathan; Wymer, Kevin; Chang, Yu-Hui; Lim, Elisabeth; Adeleye, Olufunmilola; Humphreys, Mitchell R.; Stern, Karen L.
Abstract : Abstract : Purpose: Post-ureteroscopy stent placement carries significant morbidity which can interfere with daily life. This discomfort unfortunately leads to high utilization of opioid pain medications, which have a known risk of addiction. Cannabidiol oil represents an alternative analgesic that has proven anti-inflammatory and antinociceptive effects. The purpose was to evaluate the effect of a Food and Drug Administration–approved cannabidiol oil (Epidiolex) on pain control and opioid usage in the post-ureteroscopy setting. Materials and Methods: This was a prospective, randomized, double-blind, placebo-controlled trial at a tertiary care center. Ninety patients undergoing ureteroscopy with stent placement for urinary stone disease were randomized 1:1 to placebo or 20 mg cannabidiol oil daily for 3 days postoperatively. Both groups were prescribed a rescue narcotic, tamsulosin, oxybutynin, and phenazopyridine. Daily pain scores, medication usage, and ureteral stent symptoms using the validated Ureteral Stent Symptom Questionnaire were recorded postoperatively. Results: Both the placebo and cannabidiol oil groups were not different in pre- and perioperative characteristics. There was no difference in pain scores or opioid usage between groups postoperatively. The level of discomfort with ureteral stents was also not different between groups when comparing physical activity, sleep, urination, and activities of daily life. Conclusions: This randomized, blinded, placebo-controlled trial showed that cannabidiol oil is safe but ineffective when compared to placebo in reducing post-ureteroscopic stent discomfort or opioid usage. Despite the availability of numerous analgesic agents, stent symptoms continue to be a dissatisfier for most patients, suggesting additional work needs to focus on novel interventions and pain control.